Comparison of Two Techniques to Measure Optic Nerve Sheath Diameter in Patients at Risk for Increased Intracranial Pressure. Issue 6 (June 2019) - Agrawal, Ashish; Cheng, Roger; Tang, Julin; Madhok, Debbie Y.
Abstract : Objectives: Intracranial pressure over 20 mm Hg is associated with poor neurologic prognosis, but measuring intracranial pressure directly requires an invasive procedure. Dilation of the optic nerve sheath on axial ultrasound of the eye has been correlated with elevated intracranial pressure, but optimal cutoffs have been inconsistent possibly related to the measurement technique. A coronal technique has been studied on healthy volunteers but not on patients with high intracranial pressure. We compared two measurement techniques (axial and coronal) in patients with suspected high intracranial pressure due to trauma, bleeding, tumor, or infection. Design: Prospective blinded observational study. Setting: Two tertiary referral center ICUs. Patients: Twenty adults admitted to the ICU at risk for increased intracranial pressure expected to receive invasive intracranial monitoring. Interventions: Ultrasound measurements of the optic nerve sheath in axial and coronal views either averaged between eyes or the highest in either eye. Measurements and Main Results: Coronal measurements showed less variability between each eye than axial measurements (mean difference 0.5 mm vs 1 mm; p = 0.03) and were associated with high intracranial pressure at first measurement and over 24 hours (area under the receiver operating characteristic range 0.7–0.8). Mean and highest axial measurements showed improved association with first (area under the receiver operating characteristic 0.87–0.94) and highest intracranial pressure measurement (area under the receiver operating characteristic 0.89–0.96) within 24 hours. A cutoff of highest axial measurement in either eye greater than 6.2 mm or mean axial measurement between eyes of 5.6 mm had a sensitivity of 100% in predicting high intracranial pressure over the following 24 hours. Conclusions: The highest axial measurement of optic nerve sheath diameter in either eye is the most predictive of patients with high intracranial pressure in our population. This comparison of measurement techniques has not previously been described and should be further explored to set test cutoffs for ultrasound of the optic nerve sheath diameter.